(3CeGdj GHf OQjOs - (3eMeO Hf GdMSf Hf OQjO GdCROj, CHh HcQ, GHf OQjO,J (B321 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3bGd CHhHcQ Hf OQjO(B: (3CNHQfG CHhYKeGf, Yf GdJhRj, deG cGf jhe GdLed hEdJbi GdfGS NQL QLd ef Hfj CSO adbi eMeO GHf WdMI Hf YHjOGddg hcGf jSei GdSLGO s
(3BNQgG (B:s
(3aZVH eYGhjI hbGd dg(B: (3eG CfJ hPGc CjgG GdYHO aCeG GdBf abGFdgG CMb HgG, gPG BNQ GdLRA GdSGHY ef CeGdj GHf OQjO hGdMeO ddg QH GdYGdejf s
(3QhGjI CHj eSde eMeO Hf Ydj GdcGJH Yfgs
(3gfGc Tc aj Cf GdeNWhW gh JYdjb ef CeGdj GHf OQjO hdjS GdCeGdj faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
Keywords: (3GdCOHs